Curcumin and quercetin modify warfarin-induced regulation of porcine CYP1A2 and CYP3A expression and activity in vitro - Burkina, Viktoriia; Zamaratskaia, Galia; Rasmussen, Martin Krøyer (Xenobiotica, 2022)
The anticoagulant drug warfarin is used treat atrial fibrillation. Several cases of drug-drug and drug-food interactions have been reported for warfarin.The aim of this study was to investigate the interaction between simultaneous administration of warfarin with the two ubiquitous flavonoids quercetin and curcumin.Using porcine primary hepatocytes we demonstrated that warfarin treatment increased the mRNA and protein expression of CYP3A(29), while no changes in CYP1A2 were observed. Co-treatment with quercetin and/or curcumin decreased the warfarin-induced CYP3A protein expression. Moreover, when quercetin and curcumin were co-administrated to warfarin-exposed hepatocytes the protein expression of CYP1A2 was decreased. In hepatic microsomes, curcumin inhibited the activity of both CYP1A2 and CYP3A, while warfarin had no effect. Both quercetin and curcumin decreased the CYP1A2 and CYP3A activity when co-administrated with warfarin.The results clearly demonstrated that quercetin and curcumin can cause food-drug interactions with warfarin, and that the cocktail effect of exposure to more compounds than one can further enhance these interactions.
Keywords: Swine; cytochrom P-450 CYP1A2; jaterní mikrozomy; Cytochrome P-450 CYP3A; Cytochrome P-450 CYP1A2; cytochrom P-450 CYP3A; Curcumin; Cytochrome P-450 Enzyme System; Microsomes, Liver; Animals; prasata; quercetin; zvířata; warfarin; systém (enzymů) cytochromů P-450; Warfarin; kurkumin; Quercetin